If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + v = 3 Solving -2 + v = 3 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + v = 3 + 2 Combine like terms: -2 + 2 = 0 0 + v = 3 + 2 v = 3 + 2 Combine like terms: 3 + 2 = 5 v = 5 Simplifying v = 5
| 9x-88=2x-11 | | Y/3-12=8 | | 4[3+2(x+5)]=76 | | 29+8(q-11)=-12 | | 5x-1(-7x+9)=15 | | (4w^2-15)-(-15w^2)= | | 0.75m-0.5=2+0.25m | | 0.71m-0.5=2+0.25m | | 3x-54=-2 | | 6x+3y=190 | | f(x)=-2senx | | 18x-(4x-2)=142 | | 4d=-8+3d | | D-9.8=-3.2 | | 6x^3+19x^2+15x-28=0 | | D-9.8=3.2 | | 1.2(x)=9.9-1.2(x) | | 2x+(-10)=-2 | | 6p=5p+6 | | 80+-8k=2k | | -3x-6=-6x+9 | | 6x^3+19x^2+15x-28= | | -1/7m-2=-13 | | -3x-24=5 | | -2/4d-4-4=5 | | 7y-4=6y-3 | | 7m+5=-9 | | 0+P(0)+650+P(650)= | | 5p+5=20 | | -15m+4m=m | | 3x-2/-4=10 | | 3(t-11)=2(t+8) |